Association of Epileptiform Discharge and Autism Spectrum Disorder Severity in Children Attending the Outpatient Clinics, Child Welfare Teaching Hospital, Baghdad - Abdulrazaq, Esraa E.; Saeed, Ghassan Th. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Subjects with Autism Spectrum Disorder (ASD) have a higher prevalence of seizures than the general population, according to a significant body of research. Also, seizure-free patients with ASD have been found to have a higher prevalence of epileptiform discharge abnormalities compared to healthy controls across investigations. Changes in the electroencephalogram (EEG) can manifest as sharp waves or spikes, sharp and slow waves, generally distributed or general area, or focused, and can manifest in various brain regions. There is a necessity to search for a distinctive EEG characteristic in ASD patients.Objectives: This study used electroencephalography to investigate the relationship between interictal epileptiform discharges and the severity of ASD in children.Methods: The study involved a total of 65 children. The first group consisted of 30 children (seven females and 23 males, 2-12 years of age) recruited from the autism centre and the paediatric neurology consultancy clinic in the Child Welfare Teaching Hospital / Medical City. The second group consisted of 35 age- and gender-matched normally developed children (10 females and 25 males, 2-12 years of age) recruited from the Paediatrics Consultation Clinics in the Child Welfare Teaching Hospital. The ASD children met the DSM-5 criteria for autism, and the Childhood Autism Rating Scale was utilised to determine the severity of autism. The electroencephalography signals were recorded to detect epileptiform discharge. The data was collected during the period from 5th October 2022 to 1st April 2023.Result: A statistically significant association was found between the epileptiform discharges and the study group (ASD vs. normally developed children). The EEG records were normal in 20 (66.7%), abnormal in the form of focal epileptiform discharge in 5 (16.7%), and in the form of generalised epileptiform discharge in 5 (16.7%) of ASD children. The EEG findings and the CARS-measured autism severity showed a statistically significant association (P=0.05), as the EEG abnormalities increased with the severity of autism.Conclusion: The degree of autism was found to be associated with the abnormalities of the electroencephalogram and the degree of autism.